(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Management of ectopic pregnancy is very crucial issue for the survival of the patients. Objective: The purpose of the present study was to observe the surgical management and per-operative findings of women with ectopic pregnancy. Methodology: This cross-sectional study was carried out in the inpatient Department of Obstetrics and Gynaecology at Bangladesh Medical College Hospital, Dhaka, Bangladesh from January 2009 to December 2009 for a period of one (1) year. All clinically suspected cases of ectopic pregnancy within the reproductive age admitted in the department of Obstetrics and Gynaecology at the Bangladesh Medical College Hospital, Dhaka were included in the present study. In most of the cases, laparoscopy or laparotomy was done to confirm the diagnosis and manage the cases. Result: A total number of 48 cases of ectopic pregnancy women were recruited for this study. The highest number of ectopic pregnancy occurs in the ampulla of the fallopian tube which was 27(58.3%) cases. The right tube had been found to be affected more than the left which was 30(62.5%) cases and 18(37.5%) cases respectively. Most of the patients were presented with ruptured tubal pregnancy which was 30(62.5%) cases. Opposite tube was normal looking in 25(52.1%) cases. Unilateral salpingectomy and salpingectomy with contra lateral tubectomy were operated in 32(66.7%) cases and 10(20.8%) cases respectively. Conclusion: In conclusion most of the ectopic pregnancy is occurred in the site of ampulla of fallopian tube in right side which are mostly surgically managed by unilateral salpingectomy. Journal of Current and Advance Medical Research 2020;7(1): 12-16